Pengalaman Perawat Saat Menghadapi Gempa Bumi: A Systematic Review - Yanuar Aga Nugraha; Tintin Sukartini; Ferry Efendi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Background: Earthquake disaster can damage everything and threaten human life. Nurses play a major role to rescue victims during earthquake. Nurses play a major role to rescue victims when a disaster occurs. Thus, nurses’ response is needed in facing an earthquake. Objective: to find out nurses’ experiences in facing the earthquake. Methods: Systematic Review was prepared using Preffered Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Database used in this study were Scopus, Proquest and Science direct in the last 5 years from 2014 to 2019, full text article and in English. Keywords used in this study were “nurse OR public health nurse OR community nurse” AND “disaster OR natural disaster OR earthquake” AND “experience OR experience of life”. This systematic review used 10 articles that fit the inclusion criteria. Results: Of the 10 articles used in this study, the results indicated that nurses’ experiences in coping with earthquake were dillema experienced by nurses, lack of disaster preparedness, limited tools, psychological problem, and fear of aftershocks. Conclusion: Nurses had various experiences in responding to earthquake disaster and they need more careful preparation in preparing for earthquake. Keywords: disaster; earthquake; nurse ABSTRAK Latar belakang: Gempa menjadi bencana yang dapat merusak segalanya dan mengancam kehidupan manusia. Perawat menjadi pemegang kunci penyelamat korban ketika terjadi bencana. Sehingga diperlukan respon perawat dalam menghadapi bencana gempa bumi. Tujuan: untuk mengetahui pengalaman perawat saat menghadapi gempa bumi. Metode: Systematic Review ini disusun menggunakan Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Database yang digunakan yaitu Scopus, Proquest dan Science Direct yang dibatasi 5 tahun terakhir dari 2014 hingga 2019, full text article dan berbahasa Inggris. Kata kunci yang digunakan yaitu “nurse OR public health nurse OR community nurse” AND “disaster OR natural disaster OR earthquake” AND “experience”. Systematic review ini menggunakan 10 artikel yang sesuai dengan kriteria inklusi. Hasil: dari 10 artikel yang digunakan telah didapatkan hasil tema pengalaman perawat dalam mengadapi bencana alam gempa antara lain dilema yang dirasakan oleh perawat, kurangnya pelatihan bencana, keterbatasan alat, masalah psikologis, dan takut akan datangnya gempa susulan. Kesimpulan: Berbagai pengalaman perawat ketika merespon bencana gempa bumi dan diperlukan persiapan lebih matang lagi untuk perawat dalam mempersiapakan menghadapi bencana gempa bumi. Kata kunci: bencana; gempa bumi; perawat